Embriões de galinha como modelo experimental para testes com fármacos e vírus - Sommerfeld, Simone (2021)
For many years the chicken embryo (CE) has been a widely used animal model, however, there is a constant lack of standardization in the use of these animals. Thus, the objective of this study is to verify if macroscopic, histopathological, blood count, metabolic changes and oxidative stress in CE of different ages are peculiar to the model, proposing the need for standardization based on two drugs and a virus that cause known changes in other animals. The CE were incubated at 37ºC and 58% humidity and turned automatically every two hours. At 10 embryonic incubation da ys (EID), CE were inoculated with Gammacoronavirus in allantoic fluid having the negative control (NC) in parallel. For drug testing, inoculations were performed with Filgrastim (FG) (150µg/CE) and dexamethasone (DX) (0.08µg/EG) and a NC group at the ages of 0, 3, 7, 10 and 12 EID via shell membrane (SM) and chorioallantoic membrane (CAM). CE were weighed and mortality and macroscopic lesions were assessed. In addition, samples were collected for biochemical, hematological, histopathological and oxidative stress analysis. The response of embryos to challenges with viruses and drugs does not always go as expected. Although macroscopic and microscopic changes were visible in those infected, white blood cell counts and inflammation biomarkers such as C-reactive protein did not change. It is important to note that some drugs may not result in expected effects for CE as seen in FG treatment. For embryos treated with DX, changes in blood parameters and biomarkers seem to be inherent in the model and are dependent on the stage of CE development.